The Literature and Policy Review of the Implementation of Green Hospital Concept in Indonesia - Intarti, Wiwit Desi; Khan, Muhammad Uzair; Maretalinia, Maretalinia (THRIVE Health Science Journal, 2024)
The Green Hospital Model is crucial for aligning healthcare facilities with sustainable development goals. Implementing green initiatives in hospitals in Indonesia faces challenges despite the country's efforts to improve healthcare infrastructure and services. This study aimed to review pieces of literature (abroad and in Indonesia) and policies and regulations related to green hospitals in Indonesia. This study carried out some literature and policies to compare and have a deep understanding of stakeholders’ role in collaborating to implement the green hospital in Indonesia. Totally 7 journal articles from outside and inside Indonesia were included in this study from databases Science Direct and Scholar Google. Moreover, the policies and regulations are found in Google and Scholar Google. The results found that there is no role model and representative of green hospitals in Indonesia to lead other hospitals. The limited collaboration between stakeholders is also an issue. The conclusion includes the preparedness of the government to seriously implement the green hospital.